User-centered development of a hypospadias decision aid prototype. Issue 5 (October 2020) - Chan, Katherine H.; Misseri, Rosalia; Carroll, Aaron; Frankel, Richard; Moore, Courtney M.; Cockrum, Brandon; Wiehe, Sarah E.
Summary: Introduction: Many parents who choose hypospadias repair for their sons experience decisional conflict (DC) and decisional regret (DR). We previously found that parental decision-making about hypospadias surgery is a complex process characterized by cyclic information-seeking to alleviate anxiety and confusion. Objective: The objective of this study was to engage parents of hypospadias patients and pediatric providers in the co-design of a decision aid (DA) prototype to facilitate shared decision-making about hypospadias surgery and address DC and DR. Methods: From August 2018 to January 2019, we conducted three co-design workshops with parents of hypospadias patients, pediatric urology and general pediatric providers to discuss their recommendations for a DA prototype. Activities were audio recorded and professionally transcribed. Transcripts and worksheets were analyzed by six coders using qualitative analysis to identify key aspects of a hypospadias DA desired by stakeholders. We conducted a collaborative design and prototyping session to establish key features and requirements, created a content map visualizing this work, and then developed a DA prototype. Results: Parent participants included 6 mothers and 4 fathers: 8 Caucasian, 2 African-American; median age 31 years. Providers included pediatric urology (n = 7) and general pediatric providers (n = 10): median age 47.5 years, 83.3% Caucasian, 58.3% male, 58.3% MD's and 41.7% nurse practitioners. Participants created user-friendly, interactive DA prototypes with "24/7" availability that had three key functions: 1) provide accurate, customizable, educational content, 2) connect parents with each other, and 3) engage them in a decision-making activity. The prototype consisted of five modules (Extended Summary Figure). "Hypospadias Basics" includes epidemiology and a hypospadias severity scale. "Surgery Basics" includes goals, illustrated steps, and pros/cons of surgery. "Testimonials" includes videos of parents and adolescents discussing their experiences. "Help me Decide" includes a decisional conflict scale and a decision-making activity (i.e. values clarification method). "Frequently Asked Questions" covers general hypospadias information, perioperative expectations and a review of postoperative care. Discussion: To our knowledge, this is the first DA prototype developed for a pediatric urology condition using a human-centered design approach to engage many key stakeholders in the development process. One limitation of this study is the small population sampled, which limits generalizability and means that our findings may not reflect the views of all parents or pediatric providers involved in hypospadias decision-making. Conclusions: We created a parent-centered hypospadias DA prototype that provides decision support in an online, interactive format. Future directions include further testing with usability experts, providers and parents. Summary Figure Summary Figure